(untitled) (UNIHumanitas, 2024)
The research conducted sought to obtain new knowledge about the implementation of inclusive education in universities in the city of Encarnación exclusively in terms of physical barriers, i.e. infrastructure. It focused on studying the phenomenon in its natural context, reviewing the research conducted on the subject in the last five years, specifically in Encarnación. The research approach was qualitative, descriptive and cross-sectional. The study population consisted of university executives from the universities sampled in the city of Encarnación. The techniques used were interviews and observation. Regarding the results obtained, in recent years, the universities have been carrying out structural constructions; that is, an improvement of the physical infrastructure towards inclusiveness. As for the curricular adjustments, in order to respond to the inclusive approach, they are established in the Institutional Educational Projects (PEI) as determined by Law 5136/13, in the universities studied and foreseen in their budget, which allows these higher education institutions to respond to the requirements and regulations of the Law of Inclusive Education.